Audio Coding Using Overlap and Kernel Adaptation - Helmrich, Christian; Edler, Bernd (IEEE Signal Processing Letters, 2016)
Perceptual audio coding schemes typically apply the modified discrete cosine transform (MDCT) with different lengths and windows, and utilize signal-adaptive switching between these on a perframe basis for best subjective performance. In previous papers, the authors demonstrated that further quality gains can be achieved for some input signals using additional transform kernels such as the modified discrete sine transform (MDST) or greater inter-transform overlap by means of a modified extended lapped transform (MELT). This work discusses the algorithmic procedures and codec modifications necessary to combine all of the above features-transform length, window shape, transform kernel, and overlap ratio switching-into a flexible input-adaptive coding system. It is shown that, due to full time-domain aliasing cancelation, this system supports perfect signal reconstruction in the absence of quantization and, thanks to fast realizations of all transforms, increases the codec complexity only negligibly. The results of a 5.1 multichannel listening test are also reported.<br

Efficient Transform Coding of Two-Channel Audio Signals by Means of Complex-Valued Stereo Prediction - Helmrich, Christian; Carlsson, Pontus; Disch, Sascha; Edler, Bernd; Hilpert, Johannes; Neusinger, Matthias; Purnhagen, Heiko; Rettelbach, Nikolaus; Robilliard, Julien; Villemoes, Lars F. (Proceedings of the IEEE 2011 Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
Keywords: Decoding; Transforms; Complexity theory; Audio coding; Transform coding; Compaction; Audio coding; MDCT; M/S stereo; prediction

Improved Low-Delay MDCT-Based Coding of Both Stationary and Transient Audio Signals - Helmrich, Christian; Marković, Goran; Edler, Bernd (Proceedings of the IEEE 2014 Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2014)
General-purpose MDCT-based audio coders like MP3 or HE-AAC utilize long inter-transform overlap and lookahead-based transform length switching to provide good coding quality for both stationary and non-stationary, i. e. transient, input signals even at low bitrates. In low-delay communication scenarios such as Voice over IP, however, algorithmic delay due to framing and overlap typically needs to be reduced and additional lookahead must be avoided. We show that these restrictions limit the performance of contemporary low-delay transform coders on either stationary or transient material and propose 3 modifications: an improved noise substitution technique and increased overlap between “long”transforms for stationary, and “long to short” transform length switching without lookahead and directly from the long overlap for transient frames. A listening test indicates the merit of these changes when integrated into AAC-LD.<br

Intelligent Gap Filling in Perceptual Transform Coding of Audio - Disch, Sascha; Niedermeier, Andreas; Helmrich, Christian; Neukam, Christian; Schmidt, Konstantin; Geiger, Ralf; Lecomte, Jérémie; Ghido, Florin; Nagel, Frederik; Edler, Bernd (141th AES Convention, 2016)
Intelligent Gap Filling (IGF) denotes a semi-parametric coding technique within modern codecs like MPEG-H-3D-Audio or the 3gpp-EVS-codec. IGF can be applied to fill spectral holes introduced by the quantization process in the encoder due to low-bitrate constraints. Typically, if the limited bit budget does not allow for transparent coding, spectral holes emerge in the high-frequency (HF) region of the signal first and increasingly affect the entire upper spectral range for lowest bitrates. At the decoder side, such spectral holes are substituted via IGF using synthetic HF content generated out of low-frequency (LF) content, and post-processing controlled by additional parametric side information. This paper provides an overview of the principles and functionalities of IGF and presents listening test data assessing the perceptual quality of IGF coded audio material.<br

Low-Complexity Semi-Parametric Joint-Stereo Audio Transform Coding - Helmrich, Christian; Niedermeier, Andreas; Bayer, Stefan; Edler, Bernd (Proceedings, 23rd European Signal Processing Conference (EUSIPCO 2015), 2015)
Traditional audio codecs based on real-valued transforms utilize separate and largely independent algorithmic schemes for parametric coding of noise-like or high-frequency spectral components as well as channel pairs. It is shown that in the frequency-domain part of coders such as Extended HE-AAC, these schemes can be unified into a single algorithmic block located at the core of the modified discrete cosine transform path, enabling greater flexibility like semi-parametric coding and large savings in codec delay and complexity. This paper focuses on the stereo coding aspect of this block and demonstrates that, by using specially chosen spectral configurations when deriving the parametric side-information in the encoder, perceptual artifacts can be reduced and the spatial processing in the decoder can remain real-valued. Listening tests confirm the benefit of our proposal at intermediate bit-rates.<br

Signal-Adaptive Switching of Overlap Ratio in Audio Transform Coding - Helmrich, Christian; Edler, Bernd (2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2016)
Contemporary perceptual audio coders, all of which apply the modified discrete cosine transform (MDCT), with an overlap ratio of 50%, for frequency-domain quantization, provide good coding quality even at low bit-rates. However, relatively long frames are required for acceptable low-rate performance also for quasi-stationary harmonic input, leading to increased algorithmic latency and reduced temporal coding resolution. This paper investigates the alternative approach of employing the extended lapped transform (ELT), with 75% overlap ratio, on such input. To maintain a high time resolution for coding of transient segments, the ELT definition is modified such that frame-wise switching between ELT (for quasi-stationary) and MDCT coding (for non-stationary or non-tonal regions), with complete time-domain aliasing cancelation and no increase in frame length, becomes possible. A new ELT window function with improved side-lobe rejection to avoid framing artifacts is also derived. Blind subjective evaluation of the switched-ratio proposal confirms the benefit of the signal-adaptive design.<br

Signal-Adaptive Transform Kernel Switching for Stereo Audio Coding - Helmrich, Christian; Edler, Bernd (2015 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA), 2015)
Modern stereo and multi-channel perceptual audio codecs utilizing the modified discrete cosine transform (MDCT) can achieve very good overall coding quality even at low bit-rates but lack efficiency on some material with inter-channel phase difference (IPD) of about ±90 degrees. To address this issue a generalization of the lapped transform coding scheme is proposed which retains the perfect reconstruction property while allowing the usage of three further transform kernels, one of which is the modified discrete sine transform (MDST). Blind listening tests indicate that by frame-wise adaptation of each channel's transform kernel to the instantaneous IPD characteristics, notable gains in coding quality are possible with only negligible increase in decoder complexity and parameter rate.<br